Phylogenetic relationships within the cosmopolitan buckthorn family (Rhamnaceae) support the resurrection of Sarcomphalus and the description of Pseudoziziphus gen. nov. Issue 1 (13th November 2015) - Hauenschild, Frank; Matuszak, Sabine; Muellner-Riehl, Alexandra N.; Favre, Adrien
Abstract: Uncertainties persist in the delineation of tribes and genera within the cosmopolitan and species‐rich Rhamnaceae. In this family, the identification of tribes and genera largely depends on combinations of traits rather than single synapomorphies, diagnostic morphological features being often shared among several clades. When taxonomic treatments based on morphological traits are in conflict with each other, phylogenetic reconstructions can help to guide taxonomic efforts. In this study, we present the largest molecular dataset to date for Rhamnaceae, by combining trnL‐trnF and ITS sequence data for more than 400 taxa, either newly sequenced or retrieved from GenBank. Our sampling design includes all 11 Rhamnaceae tribes and 57 genera. We used fasttree‐like searches, maximum likelihood estimates, and Bayesian analyses to generate a consensus phylogeny. Our reconstructions support most of the tribes as monophyletic, except Paliureae. Similarly, our analyses show the monophyly of most genera, with the exception of Ziziphus which appears to be paraphyletic. To preserve its monophyly, some species are excluded from Ziziphus and either attributed to the resurrected genus Sarcomphalus or to Pseudoziziphus, which is newly described here. Finally, our study highlights remaining uncertainties concerning phylogenetic relationships within Rhamnaceae, and identifies genera for which an increased sampling effort is encouraged.